Emulador eletrônico de um sistema de geração eólica baseado no Gsip interligado à rede elétrica trifásica por meio de um conversor back-to-back - Previero, Gabriel Ramos (2022)
This work presents a study and implementation of an electronic emulator of a wind generation system (EE-WGS), which is based on mathematical models of a wind turbine, composed of a permanent magnet synchronous generator. The management of electrical power generated from the mathematical model of wind generator (MMWG) is performed by a back-to-back converter (rectifier/inverter), which is responsible for controlling the power drained and injected into the three-phase power grid. The first stage of this converter is composed of a controlled rectifier, that is responsible for draining sinusoidal currents from the grid whose amplitudes are defined by a reference generation system, based on the MMWG, which also involves maximum power point tracking. For this, during this work, MPPT (Maximum Power Point Tracking) techniques are addressed for optimizing the performance of the full wind system. A three-phase inverter is used in the last stage of the back-to-back converter, which control the DC bus voltage and the current injection into the grid, calculated by the MMWG. In addition, the mathematical modeling of the converters in the synchronous reference frame are demonstrated, as well as the DC bus, in order to obtain the plants of the voltage and current control systems, and consequently, the controllers dimensioning. For validation of proposed EE-WGS, simulation and experimental results are showed, to demonstrate the static and dynamic behaviors of a complete wind system, as well as evaluating the performance of the system acting with MPPT trackers, which allows analyzing the efficiency of the algorithms.